Mutu Organoleptik dan Total Bakteri Asam Laktat Yogurt Sari Jagung dengan Penambahan Susu Skim dan Karagenan - Premy Puspitawati Rahayu; Ria Dewi Andriani (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2018)
The objective of this research was to analyze sensory evaluation quality and total lactic acid bacteria of corn yogurt added with skim milk and carrageenan. This research used experimental laboratory method with completely randomized design and four replications. The treatment used were skim milk with concentration (2.5; 3; 3.5% b/v) dan carrageenan (0.5; 0.75; 1 % b/v). The result showed that the treatment gave significant different effect (p <0,05) on sensory evaluation quality from texture aspect; the addition of various concentrations of skim milk, and carrageenan concentrations, and the interaction did not give a different effect (p>0.05) on the total lactic acid bacteria, organoleptic (aroma and color). The addition of various of skim milk, and carrageenan concentrations gave total of total lactic acid bacteria, organoleptic (color, aroma and texture) was 2.83 x 108-4.4 x 108 CFU/ml; white to yellowness; acidness to acid; and thickness to thick. The best treatment of this research is the addition of skim 5% and carrageenan 0.75% with total lactic acid bacteria 4.4 x 108, the aroma is acidness, the color is yellowness, the texture is thickness. It could be concluded that the addition of skim milk and carrageenan in corn yogurt production can be accepted by consumers and increase the activity of lactic acid bacteriaÂ